Respon Pertumbuhan dan Hasil Padi Sawah Organik Terhadap Residu Berbagai Macam Aplikasi Pupuk Hijau Glirisidia - Marti Winarni (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2021)
Abstract— The object of the study was to obtain the residual the various of application of Glirisidia green manures on the growth and yield of organic rice lowland. The pot experiment was carried out in a randomized complete block design (RCBD) consisting of one factor and three replications. The factor was 10 residual the various of application of Glirisidia leaves that added the compost of cattle manures, namely: 100% fresh Glirisidia leaves+0% compost; 60% fresh Glirisidia leaves+40% compost; 40% fresh Glirisidia leaves+60% compost; 100% wind-dried Glirisidia leaves+0% compost; 60% of wind-dried Glirisidia leaves+40% compost; 40% wind-dried Glirisidia leaves+60% compost; 100% sun-dried Glirisidia leaves+0% compost; 60% of the sun-dried Glirisidia leaves+40% of compost; 40% of the sun-dried Glirisidia leaves+60% compost; and 0% Glirisidia leaves+100% compost. The results showed that the residual of Glirisidia leaves given in the form of fresh, wind-dried and sun-dried with a composition of 60% Glirisidia green manures+40% compost, 40% composition of Glirisidia green manures + 60% compost and 100% compost without Glirisidia leaves supported growth, yield components and yield of organic lowland rice (an average of 140. g/hill) is higher than that of Glirisidia leaves 100% without added of cow manures (an average of 124.29 g/hill). Keywords—: Glirisidia leaf; green manure; organic lowland rice; residue.